Double blind placebo controlled trial of pulse treatment with methylprednisolone combined with disease modifying drugs in rheumatoid arthritis. Issue 6746 (4th August 1990) - Hansen, T M; Kryger, P; Elling, H; Haar, D; Kreutzfeldt, M; Ingeman-Nielsen, M W; Olsson, A T; Pedersen, C; Rahbek, A; Tvede, N
Abstract : OBJECTIVE--To assess whether monthly treatment with intravenous methylprednisolone enhances or accelerates the effect of disease modifying drugs in patients with rheumatoid arthritis. DESIGN--A 12 month double blind, placebo controlled, multicentre trial in which patients with active rheumatoid arthritis were randomly allocated to receive pulses of either methylprednisolone or saline every four weeks for six months. At the start of the pulse treatment all patients were started on penicillamine or azathioprine. SETTING--Four rheumatology departments in Denmark. PATIENTS--97 Patients (71 women, 26 men) aged 23-84 (mean 60) who had active rheumatoid arthritis of at least four weeks' duration despite treatment with non-steroidal anti-inflammatory drugs. MAIN OUTCOME MEASURES--Monthly clinical recording of morning stiffness, number of tender and swollen joints, blinded observers' evaluation of therapeutic effect, and patients' self assessed condition. Concomitant laboratory measurements of erythrocyte sedimentation rate and concentrations of C reactive protein and haemoglobin. Radiography to determine the number of erosions at the start of treatment and after 12 months. RESULTS--57 Patients completed the trial, taking the same disease modifying drug throughout. Evaluation four weeks after each pulse treatment and at 12 month follow up showed no significant differences between the methylprednisolone and placebo groups in any of the clinical or laboratory variables. Radiography showed the same degree of progression of erosions in both groups. Evaluation of the total data on 97 patients and on the 57 who completed the trial showed the same lack of significance between the treatment groups. CONCLUSIONS--Intravenous pulse treatment with steroids can be recommended only for rapid temporary relief of flares of disease in patients with rheumatoid arthritis. The response is short lived. Repeated pulses of methylprednisolone at four week intervals do not improve the results of treatment with drugs that induce remission such as penicillamine and azathioprine.